PENERAPAN MODEL GROUP INVESTIGATION DENGAN MEDIA KONKRET DALAM PENINGKATAN PEMBELAJARAN IPA TENTANG ENERGI PADA SISWA KELAS IV SDN 1 KARANGPOH TAHUN AJARAN 2014/2015 - purnamasari, menik (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract: The Application of Model Group Investigation Type Using Media Concrete in Improving Natural Science Learning about Energy for the fourGrade Students of Elementary School. The objectives of the research are: (1) to describe the steps of model Group Investigation type using media concrete, (2) to improve Natural Science learning about energy, and (3) to describe its problems and solutions. This research is a collaborative Classroom Action Research (CAR) conducted in three cycle. Each cycle consisted of planning, implementation, observation, and reflection. Subjects of this research were 24 fifth grade students of SDN1 Karangpoh. The results of the research show that the application of model Group Investigation type using media concrete that implemented with appropriate procedure can improve Natural Science learning about energy for the four grade students. Keywords: Group Investigation, media concrete, Natural Science Abstrak: Penerapan Model Group Investigation dengan Media Konkret untuk Siswa Kelas IV SD. Tujuan penelitian ini adalah mendeskripsikan langkah-langkah penerapan model Group Investigation dengan media konkret, meningkatkan pembelajaran IPA tentang energi, dan mendeskripsikan kendala serta solusinya. Penelitian ini adalah penelitian tindakan kelas kolaboratif dengan tiga siklus. Tiap siklus terdiri dari tahap perencanaan, tindakan, observasi, dan refleksi. Subjek penelitiannya adalah siswa kelas IV SDN 1 Karangpoh dengan jumlah 24 siswa. Hasil penelitian menunjukkan bahwa penerapan model Group Investigation dengan media konkret yang dilaksanakan sesuai langkah yang tepat dapat meningkatkan pembelajaran IPA tentang energi pada siswa kelas IV SD. Kata Kunci: Group Investigation, media konkret, IPA